2022
DOI: 10.1002/nme.7129
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient method for structural model reduction

Abstract: Model reduction is a commonly used method for quickly computing the lower‐order eigenvalues and eigenvectors of a structure. This article proposed a direct model reduction method without any iterations. Compared with the existing methods, the proposed technique has two main advantages. The first one is that the explicit expression of the transformation matrix can be directly obtained using a recurrence formula. The second one is that the calculation efficiency of the proposed method is very high because there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…From Equations (7) and (11), one obtains On the other hand, structural flexibility F can also be approximately obtained through structural free-vibration tests. Using the system matrices K and M, the free-vibration modes can be computed through the following generalized eigenvalue problem as [11]:…”
Section: Definition Of Structural Flexibility and Testing Methodsmentioning
confidence: 99%
“…From Equations (7) and (11), one obtains On the other hand, structural flexibility F can also be approximately obtained through structural free-vibration tests. Using the system matrices K and M, the free-vibration modes can be computed through the following generalized eigenvalue problem as [11]:…”
Section: Definition Of Structural Flexibility and Testing Methodsmentioning
confidence: 99%
“…where D( f ) represents a diagonal matrix whose diagonal element is the mass corresponding to the load vector f . Finally, Equations (10), (21), and ( 22) can be combined to construct the hybrid sensitivity system, as follows:…”
Section: The Hybrid Sensitivitymentioning
confidence: 99%
“…We note that the pure static algorithm computed the fault coefficients using Equation (10) with only static data. The pure dynamic algorithm computed the fault coefficients using Equation (21) with only dynamic data. From Figures 4-6, one can find that the fault coefficients obtained by the hybrid method more clearly indicated that the fault was located in bar element 3.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The disparities between the analytical data and the measured data for damage detection were reduced using the modal sensitivity approach based on Bayesian parameter estimation. To solve the problem of incomplete measurement, Yang and Peng developed the model condensation method [ 18 ] and proposed the modal condensation sensitivity [ 19 ] for the damage identification of beam structures. Pooya and Massumi [ 20 ] used the difference between mode shape curvature and the mode shape curvature estimation of damaged structures as an indicator to identify the damage location.…”
Section: Introductionmentioning
confidence: 99%